Developing Learning Media of the Projection Drawing to Improve the Quality of Learning Process and Outcomes - *, Mulyanto; Rakhmawati, Ani (Proceeding of International Conference on Teacher Training and Education, 2016)
The study aims to develop a media for teaching projection drawing to improve the quality of learning process and outcomes. The research was conducted at the Department of Arts Education, Faculty of Teacher Training and Education, Universitas Sebelas Maret, Surakarta, Indonesia. The study is a classroom action research consisting of two cycles. The subjects of the research are 20 students. The research manipulate the multimedia-based learning resource in the form of the power point presentation program that displays moving dot-points, lines, and colored objects, supported with sound effects. The data was collected through observation and interview, and is then analyzed using comparative technique to compare the condition before, during, and after the research. The result of the research, which is a media for teaching and learning projection drawing, consists of nine topics, including: concept of projection image plane, projection of points, projection of lines, projection of planes, projection of the surface of an object, projection of object rotated to the left, projection of object rotated to the front, projection of oblique object, and projection of truncated objects. The model of drawing sequence was presented sequentially as an integrated drawing item in which lines were displayed in different primary colors followed by a combination of motions and sound effects. To use the model effectively, the study finds that the configuration of dots and lines should be presented more precisely, each picture should be clearly drawn with identical sound in each movement, movement of curves should show the center point, each topic should be displayed per field, and each image should be followed by the description of the problem.